Microbial metabolite-driven immune reprogramming in tumor immunotherapy: mechanisms and therapeutic perspectives - Lu, Yao; Yuan, Huiping; Liang, Shaojie; Li, Debing; Jiang, Pengfei; Wang, Xian; Zhang, Ke; Liu, Dechun (Frontiers in Immunology, 2025)
The gut microbiome critically regulates antitumor immunity through its metabolic byproducts, which serve as pivotal mediators of host-microbe crosstalk in tumor immunotherapy. This review synthesizes cutting-edge evidence on how microbial metabolites—including short-chain fatty acids (SCFAs), tryptophan derivatives, and bile acids—reprogram immune cell dynamics and remodel the tumor microenvironment (TME). Mechanistically, metabolites such as butyrate and indole-3-propionic acid (IPA) enhance immune checkpoint inhibitor (ICI) efficacy by epigenetic modulation or metabolic reprogramming. Conversely, kynurenine (a tryptophan metabolite) and secondary bile acids drive resistance by polarizing macrophages toward an immunosuppressive phenotype or exhausting cytotoxic T cells. Metabolite-targeted interventions (such as probiotics, dietary modulation, and engineered microbes) show synergistic potential with ICIs, but require resolution of causal inference limitations, interindividual variability, tumor-context specificity, and dose optimization. Precision microbiome engineering, guided by multi-omics profiling and artificial intelligence, may unlock personalized strategies to overcome immunotherapy resistance.